2007
DOI: 10.1007/s10578-007-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Suicide Attempts among Korean Adolescents

Abstract: This study examined the rate of suicide attempts and relevant variables and identified risk factors for suicide attempts among Korean adolescents. A cross-sectional study was performed using an anonymous, self-report questionnaire. A total of 2,100 Korean adolescents, including 1,321 student adolescents and 779 delinquent adolescents, were selected using a proportional stratified random sampling method for this study. The results showed the rate of suicide attempts to be 11.6%, with delinquent adolescents repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
4
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(73 citation statements)
references
References 38 publications
6
53
4
10
Order By: Relevance
“…Depression has formerly been identified as a predictor of suicide attempts [36] and we found strong support for the hypothesis that depression leads to suicidal ideation. Depression is the strongest predictor of suicidal ideation; the amount of 30% of the variance explained in the logistic regression means that the contribution of depression is high, indeed.…”
Section: Discussionsupporting
confidence: 82%
“…Depression has formerly been identified as a predictor of suicide attempts [36] and we found strong support for the hypothesis that depression leads to suicidal ideation. Depression is the strongest predictor of suicidal ideation; the amount of 30% of the variance explained in the logistic regression means that the contribution of depression is high, indeed.…”
Section: Discussionsupporting
confidence: 82%
“…These family variables are therefore generally risk factors of suicidal behavior during adolescence, which is similar to most previous reports showing adolescent suicide attempters often suffer from a greater dysfunctional family dynamic environment than nonattempters [8,12,[20][21][22].…”
Section: Stressful Family Life Events As Risk Factors Of Adolescent Ssupporting
confidence: 85%
“…This is relatively lower than the results of surveillance of adolescents in many other countries, where 4.6%-13.2% of students reported suicide attempts [11][12][13][14]. Moreover, the rate of suicide attempt in this study is lower than international means identified by Evans et al [2].…”
Section: Prevalence Of Suicide Attempts and Gender Differencecontrasting
confidence: 74%
See 1 more Smart Citation
“…In America, West et al [68] assessed the prevalence of suicide behaviors using data from the 2007 Youth Risk Behavior Survey for students in grades 9-12, and found that the prevalence of suicide attempts was 6.9%. Another cross-sectional study among Korean adolescents revealed that the prevalence of suicide attempts was up to 11.6% [72]. These results were higher than that of our study.…”
contrasting
confidence: 87%